Climate change and stock market: The systematic review for future research using TCCM and meta-analysis - Akshaya A; Gopalakrishna B. V (Sustainable Futures)
The Intergovernmental Panel on Climate Change (IPCC) and the 2016 Paris Agreement have significantly heightened global awareness of environmental issues, stimulating extensive discussions on the intersection of climate change and financial markets in major economies. This study utilized a comprehensive keyword-based database search strategy to examine existing research on climate change and the stock market, while also providing suggestions for future research avenues. From an initial pool of 1992 papers indexed in Scopus and Web of Science, 138 articles published in A* and A-rated journals on the Australian Business Deans Council Journal Quality List (ABDC-JQL) were identified as relevant for analysis. To uncover prevailing trends in this area of research, the study employed the Theory, Context, Characteristics, and Methods (TCCM) framework and the Meta regression analysis alongside the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines during the screening process. The findings indicate that rising ecological uncertainty is likely to significantly impact corporate performance, which, in turn, could negatively influence stock market dynamics. These results highlight a crucial direction for future research into the interplay between climate change and stock market behavior.